1973
DOI: 10.1021/bi00728a002
|View full text |Cite
|
Sign up to set email alerts
|

Subunit structure of rabbit skeletal muscle phosphorylase kinase

Abstract: Rabbit skeletal muscle phosphorylase kinase was treated with sodium dodecyl sulfate and fractionated by gel filtration chromatography into two peaks. Peak I was shown to consist of previously identified subunits A and B having molecular weights of 118,000 and 108,000, respectively. Peak II was shown to consist of subunit C having a molecular weight of 41,000. Peak I showed slight heterogeneity on sedimentation equilibrium. The average molecular weight for this fraction was found to be 103,000 in 0.1 % sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(45 citation statements)
references
References 25 publications
(22 reference statements)
5
39
0
1
Order By: Relevance
“…Studies have shown that activation of PhK by multiple effectors occurs concomitantly with common conformational changes in the ␣ and ␤ subunits (4 -6); moreover, the activity of free ␥ subunit is inhibited by the ␣ and ␤ subunits (7,8). It has been proposed that the ␣ and ␤ subunits of PhK impose steric constraint upon ␥ that, when removed, leads to activation of the kinase (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Studies have shown that activation of PhK by multiple effectors occurs concomitantly with common conformational changes in the ␣ and ␤ subunits (4 -6); moreover, the activity of free ␥ subunit is inhibited by the ␣ and ␤ subunits (7,8). It has been proposed that the ␣ and ␤ subunits of PhK impose steric constraint upon ␥ that, when removed, leads to activation of the kinase (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Limited tryptic proteolysis of phosphorylase kinase is known to cause extensive structural changes, both in terms of cleaving preferentially the A and B subunits [3,4,7,8] as well as generating enzyme molecules oflower molecular weight [7]. However, basic catalytic activity can be preserved following this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle enzyme was shown to be composed of three different subunit types, A, B, and C, arranged in a probable stoichiometry of (ABC)4 [3,4]; recent studies [5] have also demonstrated the presence of a fourth component, mol. wt 17 000, that appears to be identical to the Ca2+dependent regulator protein or calmodulin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations